Collusion Detection in Online Bridge - Yan, Jeff (Proceedings of the AAAI Conference on Artificial Intelligence, 2010)
Collusion is a major unsolved security problem in online bridge: by illicitly exchanging card information over the telephone, instant messenger or the like, cheaters can gain huge advantages over honest players. It is very hard if not impossible to prevent collusion from happening. Instead, we motivate an AI-based detection approach and discuss its challenges. We challenge the AI community to create automated methods for detecting collusive traces left in game records with an accuracy that can be achieved by human masters.